MENINGKATKAN KEMAMPUAN BELAJAR KOPSTAND MELALUI METODE LATIHAN SISWA KELAS X SMA NEGERI 4 AMBON - Leuna, Semmy; Fenanlampir, Albertus (Prgram Studi Pendidikan Jasmani Kesehatan dan Rekreasi, FKIP Universitas Pattimura, 2020)
This research is to find out the method is a barometer to achieve the learning objectives. Therefore, the writer is eager to do an in-depth study on improving the learning ability of the Kopstand through the training method for the students of class x SMA Negeri 4 Ambon. This research method is a classroom action research. The subjects in this study were 30 students of class x1 public high school 4 Ambon. Based on the values ​​of cycle I and cycle II, it can be concluded that for cycle I learning has not been successful because it has not met the completeness standard of 75%. of the total number of students both in cognitive, affective and psychomotor aspects. In the first cycle, the learning has gone well, the children are enthusiastic about learning, but students are still not serious about taking part in learning and there are still those who are afraid or lack confidence. Whereas in cycle II the value of learning increased due to improvements in learning so that students were able to achieve KKM ≥75